ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN KANTOR AKUNTAN PUBLIK PADA PERUSAHAAN MANUFAKTUR YANG DISEBABKAN OLEH TINDAKAN OPORTUNIS MANAJER - Roosdiana, Dara Karina (Jurnal Ilmiah Mahasiswa FEB, 2016)
The study objective is to analyze the determinant factors affecting auditor switching of manufacturing company caused by manager opportunistic action, namely audit opinion, changes in management, size of the client firm, complexity, and client’s firm growth.The sample of this study was determined using purposive sampling method. The number of population was 150 companies and the selected sample was 10 companies. This study uses a multiple regression method as a data analysis.The result showed that client’s firm growth influenced the auditor switching caused by manager opportunistic action while audit opinion, changes in management, size of the client firm, and complexity do not have impact on the auditor switching caused by manager opportunistic action.  Keywords: Auditor Switching, Audit Opinion, Changes in Management, Size of The Client Firm, Complexity, Client’s Firm Growth, Manager Opportunistic Action.